Study on the deformation characteristics of fixed droplets in an electric field environment - Haiting Liu; Zhiming Xu; Fuqiang Zhang; Bingbing Wang; Jiewen Deng (Results in Engineering)
To explore the deformation characteristics of wall-fixed droplets in an electrostatic field environment, this paper constructs a coupled numerical model of the electric field and flow field based on the Arbitrary Lagrangian-Eulerian (ALE) framework. The model's validity is verified through experiments, and the effects of electric field strength, droplet size, relative permittivity of the droplet, and contact angle on droplet deformation are discussed. The study shows that when the contact angle is 90°, the electric field has the most significant impact on droplet height, followed by the spread radius. When the plate voltage ranges from 12 kV to 16 kV, the droplet height increases by 8.79 %, the spread radius contracts by 3.04 %, and the surface area increases by 0.87 %. Changes in the contact angle significantly affect the deformation mode: when the plate voltage is 14 kV and the contact angle is greater than 78°, the droplet primarily undergoes vertical stretching. The research results lay a foundation for further studies on droplet deformation and motion in electrostatic environments.